PENINGKATAN KEMAMPUAN PENALARAN MATEMATIS SISWA MELALUI PENGGUNAAN MODEL PROBLEM POSING DI SMP SWASTA TAPIAN NAULI - Nelli Rambe; Nunik Ardiana; Muhammad Syahril Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
This study aims to improve students’ mathematical reasoning ability through using posing problem model on the topic of cube at the eighth grade students of SMP swastaTapianNauli. The research was conducted by applying Class Action Research (CAR) with 25 students as the subject. Instrument of the research was test, questionnaire, and observation. The research consists of two cycles. The first cycle showed (a) the test showed the students’ achievement of cube was 74,25, (b) the questionnaire showed the average of students’ activities was 64.40, and (c) the observation of class teacher showed the ability of researcher in using posing problem model was 100. Furthermore, the second cycle showed (a) the test showed the students’ achievement of cube was 87, (b) the questionnaire showed the average of students’ activities was 87,60 and (c) the observation of class teacher showed the ability of researcher in using posing problem model was 100. It’s concluded posing problem model was able to improve students’ mathematical reasoning abilityon the topic of cube at the eighth grade students of SMP swasta Tapian Nauli.